PENINGKATAN HASIL PEMBELAJARAN IPAS MELALUI MODEL PROBLEM BASED LEARNING (PBL) BERBASIS MEDIA CANVA PADA SISWA KELAS IV SDN 03 KANIGORO. - Melik Budiarti.,S.Sos.,MA; Asyva Hanani Fadhilah; Nurhasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was conducted to improve the learning outcomes of students at SDN03 Kanigoro on the material of social and cultural diversity in Indonesia throughthe application of the problem based learning (PBL) model assisted by Canvavideo media. This study is based on the low achievement of low student learningoutcomes with an average below the minimum completion criteria. This study aimsto determine the effect of the problem based learning (PBL) learning modelassisted by Canva video media. This study is a descriptive qualitative study. Thistype of research is Classroom Action Research (CAR). The research location is atSDN 03 Kanigoro with a sample of 24 students. The implementation of ClassroomAction Research (CAR) during the II cycle includes the planning, implementation,observation, and reflection stages. The data obtained from this study used testtechniques in the form of written test questions, pre-test, post-test and non-testtechniques, namely observation, interviews and documentation, then analyzeddescriptively qualitatively. the results of the study showed that in cycle I theaverage score was 73.9 in the category of not reaching the KKM. While in cycle IIobtained an average score of 90.2 in the high category. Thus, the indicators thathave been met with a significant increase in student learning outcomes in thematerial on social and cultural diversity in Indonesia, the video-based learningmodel assisted by Canva media is effective in improving student learningoutcomes in class.